2008
DOI: 10.1002/cphc.200800572
|View full text |Cite
|
Sign up to set email alerts
|

A Single‐Molecule Perspective on the Role of Solvent Hydrogen Bonds in Protein Folding and Chemical Reactions

Abstract: We present an array of force spectroscopy experiments that aim to identify the role of solvent hydrogen bonds in protein folding and chemical reactions at the single-molecule level. In our experiments we control the strength of hydrogen bonds in the solvent environment by substituting water (H(2)O) with deuterium oxide (D(2)O). Using a combination of force protocols, we demonstrate that protein unfolding, protein collapse, protein folding and a chemical reaction are affected in different ways by substituting H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 81 publications
2
44
1
Order By: Relevance
“…We investigated this possibility by means of kinetic solvent isotope effects caused by replacing H 2 O by D 2 O in the samples. The stronger hydrogen bonding in D 2 O is thought to increase the hydrophobic effect and stabilize proteins (53)(54)(55)(56)(57). If water dominated the entropy change during the chaperone-mediated folding reaction, the kinetic solvent isotope effect in the chaperone should be significantly different from that of the autonomous folding reaction.…”
Section: Resultsmentioning
confidence: 99%
“…We investigated this possibility by means of kinetic solvent isotope effects caused by replacing H 2 O by D 2 O in the samples. The stronger hydrogen bonding in D 2 O is thought to increase the hydrophobic effect and stabilize proteins (53)(54)(55)(56)(57). If water dominated the entropy change during the chaperone-mediated folding reaction, the kinetic solvent isotope effect in the chaperone should be significantly different from that of the autonomous folding reaction.…”
Section: Resultsmentioning
confidence: 99%
“…Using equation (2) we have predicted the pulling speed dependence of the unfolding force for six proteins from the literature, which have been studied at just one pulling 55 speed (Figure 9). The all-alpha-helical protein vascular cell adhesion molecule-1 (VCAM1) has previously been studied using AFM force extension at a pulling speed of 1000 nm/s, measuring an unfolding force of 40 pN 80 .…”
Section: mentioning
confidence: 99%
“…This entropy is reduced as the protein forms secondary or tertiary structures. Extending these native tertiary structures, to overcome the forces holding them together, has been achieved experimentally using a number of single molecule manipulation 55 techniques and requires forces of the order of piconewtons 17 . More than a decade ago, a pioneering study used an instrument called an atomic force microscope (AFM) to mechanically unravel a single molecule of the muscle protein titin 10 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are many instances where substitution with a heavier isotope results in an increase in the rate of a process, known as an inverse isotope effect, as observed in a variety of systems [17][18][19][20][21]. It has also been reported that hydrophobic effects are more pronounced in D 2 O compared with H 2 O [22,23] and the presence of D 2 O can have an effect on phase separation temperature of microemulsions [24], both of which would have an effect on the microphase separation of clusters during formation of RF gels. Hence, microstructure formation processes present in sol-gel systems, resulting from the interplay of chemical and physical processes, may be influenced by the mere presence of D 2 O, as well as the quantitative amount of D 2 O added to reaction mixtures, with the directionality of the effect also unknown; this may, therefore, limit the validity of insights about polymerisation and structure formation mechanisms obtained from previous NMR studies.…”
Section: Introductionmentioning
confidence: 99%